Cost uncertainty in an oligopoly with endogenous entry - Marco De Pinto; Laszlo Goerke (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2021)
How does cost uncertainty affect the welfare consequences of an oligopoly? To answer this question, we investigate a Cournot oligopoly in which firms produce a homogeneous commodity and market entry is feasible. Marginal costs are unknown ex-ante, i.e. prior to entering the market. They become public knowledge before output choices are made. We show that uncertainty induces additional entry in market equilibrium and also raises the socially optimal number of firms. Since the first change dominates, the excessive entry distortion is aggravated. This prediction is robust to various extensions of the analytical set-up. Furthermore, the welfare loss due to oligopoly tends to increase with uncertainty.
Keywords: D43; L13; 330; Oligopoly; Excessive Entry; Uncertainty; Welfare